2017
DOI: 10.1007/s15010-017-1101-5
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in chronic liver diseases in two cohorts of 2001 and 2014 in Italy

Abstract: This study highlights important inter- and intra-gender differences in the characteristics and etiological factors of patients with CLD in Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
2
19
3
Order By: Relevance
“…In male mean age was 49 years and in female mean age was 53 years. 8 Similar observation was made by Sagnelli E et al in which mean age in male was 52.9 years and in female 58.7 years. 9 Likewise, the mean age in the study done by Zainab S et al was 10 11 46 The main predictors of bleeding in clinical practices are: large vs small varices, red color sign, CTP class C vs CTP class A and B.…”
Section: Discussionsupporting
confidence: 80%
“…In male mean age was 49 years and in female mean age was 53 years. 8 Similar observation was made by Sagnelli E et al in which mean age in male was 52.9 years and in female 58.7 years. 9 Likewise, the mean age in the study done by Zainab S et al was 10 11 46 The main predictors of bleeding in clinical practices are: large vs small varices, red color sign, CTP class C vs CTP class A and B.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, the finding that females were significantly older than males might also refect a course in disease progression. Previous studies have shown that the liver fibrosis status of women changes with age, which may be due to changes in the reproductive status, providing some hints for the result. The study showed that male patients had different etiology distribution (hepatitis B, hepatitis C, and alcohol‐associated) and the etiologies were diversified.…”
Section: Discussionmentioning
confidence: 92%
“…18,19 In addition, the finding that females were significantly older than males might also refect a course in disease progression. Previous studies have shown that the liver fibrosis status of women changes with age, which may be due to changes in the reproductive status, 20 Therefore, less treatment measures will affect the prognosis of patients. We again recommend regular follow-up of patients with liver disease to improve early diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A cohort study of over 12,000 patients showed that males with CLD were younger (52.9 vs. 58.7 yrs.) and additionally more frequently suffered from alcoholic liver disease (11.4% vs. 6.9%) than women with CLD [146]. Researchers of this analysis have highlighted significant gender differences in terms of the etiologic factors and the onset of chronic liver disease.…”
Section: Other Pathological Conditions and Hccmentioning
confidence: 93%
“…On this basis, it can be concluded that fibrosis as a consequence of CLD may also be gender-dependent. According to Saginelli et al [146] factors such as NF-κB, STAT3 and JNK could be linkers with the onset of HCC in patients with cirrhosis. In an inflammatory mouse model (mdr2 −/− mice with cholangitis, chronic liver inflammation and finally HCC), the TNF-NF-κB axis had a pro-carcinogenic effect on the liver.…”
Section: Other Pathological Conditions and Hccmentioning
confidence: 99%